Análise da influência da educação financeira nos vieses comportamentais framing, contabilidade mental e aversão à perda - Kich, Taciane Graciele Fanck (2013)
This paper aims to investigate the influence of behavioral biases in financial education framing, mental accounting and loss aversion. Therefore, we prepared a questionnaire involving the identification of financial education and the three behavioral biases. The implementation of the survey instrument was conducted in three different samples of undergraduate students of the Federal University of Santa Maria, previously classified as high, intermediate and low level of financial education. The groups characterized as low and intermediate level of financial education confirmed their classification, and considered highlevel group, presented the intermediate grade. The framing effect was seen only in the low level of financial education, mental accounting, in all groups, however in a less expressive in the high grade group of financial education, and loss aversion was present also for three groups. However, through an individual examination for all respondents in the sample, conducted by correspondence analysis, it was found that the presence of behavioral biases is found in greater amounts in the low level of financial education.